Modern Restlessness, from Hobbes to Augustine - Busch, Peter (Religions, 2015)
Only with difficulty do modern readers grasp the full import of Augustine's confession, Restless is our heart, until it rests in you, or seriously consider that it might be true. An unexpected remedy is to be found in reading Thomas Hobbes, who introduces and defends the view of happiness that is now commonly accepted without argument. According to Hobbes, human beings find their happiness not in a single, supreme good but in many objects, the securing of which requires a lifelong quest for power. But this teaching, influential and revealing though it is, fails to satisfy. Meditating on that dissatisfaction is a first step towards more serious engagement with Augustine.